Government of the Union Territory of Goa, Daman and Diu Draft Annual Plan 1982-83 Part-II - Plan Proposals in Details - Government of Goa (Government of Goa, 1981)
The document outlines the agricultural development initiatives proposed under the Draft Annual Plan 1982–83 of the Government of the Union Territory of Goa, Daman and Diu, focusing primarily on the scheme for the multiplication and distribution of seeds to enhance agricultural productivity. The programme includes the development and operation of several seed and demonstration farms such as Kalay, Margao, Mapusa, Chinbel, Daman, Dhaven, and Koday farms, where activities include the production of quality seeds, multiplication of high yielding varieties (HYV) of crops, establishment of horticultural nurseries, and experimental trials in collaboration with the Indian Council of Agricultural Research (ICAR). These farms support the cultivation and distribution of improved varieties of crops such as paddy, ragi, maize, pulses, and sugarcane, while also promoting horticultural crops like mango, coconut, cashew, banana, pineapple, guava, and chickoo through grafting and nursery development. The High Yielding Varieties Programme aims to expand the area under improved paddy cultivation and other crops to increase production efficiency, while additional initiatives promote the diversification of crops through demonstrations for ragi, maize, jowar, and pulses to enhance yields and support multiple cropping systems. The sugarcane development programme further focuses on guiding farmers with technical cultivation practices, supplying quality planting material, conducting agronomic trials, and expanding the cultivation area to improve productivity per unit area. Infrastructure development measures such as irrigation facilities, electrification, farm roads, machinery procurement, fencing, land acquisition, and construction of office and residential facilities for farm management are also proposed to strengthen farm operations. Overall, the programme seeks to increase agricultural output, promote improved farming techniques, ensure availability of quality seeds and planting materials, and support farmers through demonstrations, research trials, and extension services across the territory.
Directorate of Planning, Statistics and Evaluation, Panaji - Goa October — 1981
Directorate of Planning, Statistics and Evaluation, Panaji - Goa October — 1981
Keywords: Agricultural Production; Seed Multiplication and Distribution; Seed Farms Development; High Yielding Varieties Programme; Paddy Cultivation; Sugarcane Development Programme; Horticulture Planting Material; Demonstration Farms; Crop Diversification; Pulse Production Programme; Agricultural Research Trials; Farm Infrastructure Development